FORMULASI LOTION ORGANIK EKSTRAK KULIT MANGGIS (GARCINIA MANGOSTANA L.) DAN UJI EFEKTIVITAS TERHADAP PH KULIT - Wempi Eka Rusmana (Jurnal Infokes, 2020)
Mangosteen peel extract contains xanthone compounds, which are bioflavonoids with properties as antioxidants, antibacterial, and antiallergic. One of the utilization of mangosteen skin extract is by making cosmetics  product in the form of organic lotion with the right formulation , formulation ingredients: (1) mangosteen skin extract, (2) Tea, (3) Acid Stearat, (4) Setyl Alcohol, (5) Glycerin, (6) Prophyl paraben, (7) Methyl paraben, (8) Parfum strawberry, (9) Aquadest with result that have organoleptic test such as shape, color, smell, and texture like lotion in general. With oil in water lotion type “O/W”. As well as having a pH value of 5 in formulations 2 (two) that competed to formulations that have a pH value of 4 in formulations 1 (one) and a pH value of 6 in formulations 3 (three)ehich can be concluded that formulations 2 (two) have a safe pH for skin that is not ready to be marketed because it has to go through several more test such as adhesion test, scatter power test,viscosity test, microbiological test as well as the effectiveness test of mangosteen skin extract for dry skin.